Real-world effectiveness of palbociclib plus fulvestrant in advanced breast cancer: Results from a population-based cohort study. (April 2022) - Cardoso Borges, Fábio; Alves da Costa, Filipa; Ramos, Adriana; Ramos, Catarina; Bernardo, Catarina; Brito, Cláudia; Mayer-da-Silva, Alexandra; Furtado, Cláudia; Ferreira, Arlindo R.; Martins-Branco, Diogo; Miranda, Ana; Lourenço, António
Abstract: Background: Real-world (RW) data may provide valuable information on the effectiveness and safety of medicines, which is particularly relevant for clinicians, patients and third-party payers. Evidence on the effectiveness of palbociclib plus fulvestrant is scarce, which highlights the need of additional studies. The aim of this study was to evaluate the effectiveness of palbociclib plus fulvestrant in advanced breast cancer (ABC). Materials and methods: We conducted a population-based retrospective cohort study and cases of interest were identified through the Portuguese National Cancer Registry database and additional data sources. Patients aged≥18 years, diagnosed with ABC and exposed to palbociclib plus fulvestrant between May 31, 2017 and March 31, 2019 were included. Patients were followed-up until death or cut-off date (February 28, 2021). Primary outcome was rw-progression-free survival (rwPFS). Secondary outcomes were rw-overall survival (rwOS), rw-time to palbociclib failure (rwTPF) and rw-time to next treatment (rwTTNT). Results: A total of 210 patients were included. Median age was 58 years (range 29–83) and 99.05% were female. Median follow-up time was 23.22 months and, at cut-off date, treatment had been discontinued in 189 patients, mainly due to disease progression (n = 152). Median rwPFS was 7.43 months (95% confidence interval [CI] 6.28–9.05) and 2-year rwPFS was 16.65% (95%CI 11.97–22.00). Median rwOS was 24.70 months (95%CI 21.58–29.27), median rwTPF was 7.5 months (95%CI 6.51–9.08) and median rwTTNT was 11.74 months (95%CI 10.33–14.08). Conclusion: Palbociclib plus fulvestrant seems an effective treatment for ABC in real-world context. Compared to registrations studies, rwPFS and rwOS were shorter in real-life setting. Highlights: Palbociclib plus fulvestrant seems to be an effective therapy for ABC in real-world. Median rwPFS and rwOS were estimated at 7.43 and 24.70 months, respectively. Our data suggest lower effectiveness in real-world than the efficacy reported. Treatment was discontinued due to AEs in 8.09% of patients, suggesting good tolerability. Registries may generate effectiveness data and support clinical and HTA decisions.